2020
DOI: 10.4314/ahs.v20i4.49
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and barriers on correct use of modified guidelines for active management of third stage of labour: a cross sectional survey of nurse-midwives at three referral hospitals in Dar es Salaam, Tanzania

Abstract: Background: Despite the fact that it is possibly preventable, postpartum haemorrhage (PPH) is the global most deadly form of obstetric bleeding, mainly sub-Saharan Africa with at least one-fourth of maternal deaths in East African regions. Active management of third stage of labour (AMTSL) is recommended to prevent PPH. However, AMTSL guidelines have been revised since 2006. Objectives: To examine the current status of nurse-midwives’ knowledge on modified AMTSL guidelines and highlight barriers to AMTSL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Regarding demographic characteristics the findings of the present study revealed that more than one third were in the age group of 30-40 years. The finding of the present study agree with (Ramadhani, Liu & Lembuka, 2020) which titled "Knowledge and barriers on correct use of modified guidelines for active management of third stage of labor: a cross sectional survey of nurse-midwives at three referral hospitals in Dar es Salaam, Tanzania" who showed more than one third were in the age group of 30-40 years.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding demographic characteristics the findings of the present study revealed that more than one third were in the age group of 30-40 years. The finding of the present study agree with (Ramadhani, Liu & Lembuka, 2020) which titled "Knowledge and barriers on correct use of modified guidelines for active management of third stage of labor: a cross sectional survey of nurse-midwives at three referral hospitals in Dar es Salaam, Tanzania" who showed more than one third were in the age group of 30-40 years.…”
Section: Discussionsupporting
confidence: 90%
“…There was substantial high maternal diastolic blood pressure, after-birth vomiting, after-birth pains, usage of analgesics until labor ward discharge, and the number of women returning to the hospital with bleeding in the active management group. A decrease in birth weight was also associated with operational management, suggesting the reduced blood volume caused by placental transfusion interference" [15]. "Consequently, it can be concluded that the appropriate management of PPH remains unknown.…”
Section: Prevention Of Pphmentioning
confidence: 99%
“…In this section we have issues of pregnancy (ectopic, 45 teenage, 46 ) labour, 47 caesarean section, 48 gestational age, 49 home delivery, 50 postpartum depression, 51 female genital mutilation in the Horn of Africa 52 and Nigeria, 53 menopause and sexuality, 54 infertility, 55 hand washing, 56 anaemia in children in Ethiopia, 57 and breastfeeding efficacy. 58 …”
Section: Reproductive and Child Health Issuesmentioning
confidence: 99%